Spray-Dried Amorphous Solid Dispersions of Atorvastatin Calcium for Improved Supersaturation and Oral Bioavailability - Jaewook Kwon; Bhupendra Raj Giri; Eon Soo Song; Jinju Bae; Junseong Lee; Dong Wuk Kim (MDPI AG, 2019)
Over the past few decades, the amorphous solid dispersions (ASDs) technique has emerged as a promising strategy to enhance the in vitro/in vivo characteristic of hydrophobic drugs. The low aqueous solubility and poor bioavailability of atorvastatin calcium (ATO), a lipid-lowering drug, present challenges for effective drug delivery. The objective of this work was to improve the aqueous solubility, in vitro dissolution, and oral absorption of ATO with amorphous solid dispersion technique prepared by spray-drying method. The optimized ternary formulation comprising of ATO; hydroxypropyl methylcellulose (HPMC), as a hydrophilic polymer; and sodium lauryl sulfate (SLS), as a surfactant, at a weight ratio of 1/1/0.1, showed significant improvement in aqueous solubility by ~18-fold compared to that of the free drug, and a cumulative release of 94.09% compared to a release of 59.32% of the free drug. Further, physicochemical studies via scanning electron microscopy, differential scanning calorimetry, and powder X-ray diffraction revealed a change from the crystalline state of the free drug to its amorphous state in the ASD. Pharmacokinetic analysis in rats demonstrated 1.68- and 2.39-fold increments in AUC and Cmax, respectively, in the ASD over the free drug. Altogether, hydrophilic carrier-based ASDs prepared by the spray-drying technique represent a promising strategy to improve the biopharmaceutical performance of poorly soluble drugs.